Ethnic fashion impressions toward Filipino ethnic-inspired apparel of selected U.P. students - Barretto, Joy Salvacion D.; Elumba, Patricia Santos (2001.)
This study is a pioneering effort in determining the impressions that selected college students have towards Filipino ethnic-inspired apparel currently available in the market. The researcher in seeking to provide a groundwork upon which further and more comprehensive studies regarding Filipino ethnic-inspired apparel can be based on. In the last three to five years, there emerged a trend of "Ethnic Renaissance" in the world of fashion. Simply put, the designers who followed this trend chose not to work with high technology fabrics and refrained from making space age decisions. Instead, they opted to reach back to the past to the histories of their countries (and others, as well) to come up with ideas to fuse with contemporary fashion. Historically in the Philippines, ethnic costumes were a reflection of a tribe's dominant traditions, values, and aspirations. In addition, they served to give identity to a tribe, to show its distinction from others. But as Philippine history unfolded and as society became more complex, the question of whether or not students today form the same impressions towards Filipino ethnic-inspired apparel that early Filipinos did towards traditional ethnic costumes must be asked. Guided by the theoretical rationale, "fashion object can be viewed as symbols possessing meaning beyond their tangible characteristics", the researcher aimed to answer the question, "What are the impressions that college students have towards Filipino ethnic-inspired apparel in the market today?" There are at present a lot of debates about what authentic ethnic apparel is. To some, contemporary ethnic inspired apparel being produced is not authentic. However, reincarnating from the past a few details of dress or a total costume without altering its form or meaning is most likely impossible. For the purpose of this study, it is assumed that Filipino-ethnic inspired apparel in the market today are adaptations, innovations, and/or reinterpretations of traditional Filipino ethnic costumes. Respondents of the study were 100 (50 seniors, 50 juniors) college students from the University of the Philippines, Diliman. The primary too that was used in conducting this research was the survey method. Because it uses sampling, data about a very large population can be obtained from a relatively small sample of people. The survey was conducted (morning and afternoon) on February 21 & 28 (Saturdays), and on March 1 (Thursday). Frequency and percentage distribution were used in determining the impressions that Filipino students have toward Filipino ethnic-inspired apparel. The results of this study confirmed the hypothesis of the researcher that Filipino students have a positive impression (82.9%) of Filipino ethnic-inspired apparel that is currently available in the market. However, these same results also reveal that regardless of this positive impressions, actual use (54%) and purchase (49%) of ethnic-inspired apparel are not as positive. The primary impressions associated to people wearing ethnic-inspired apparel (artistic, nationalistic) and ethnic fashion itself (nationalistic, shows appreciation of one's culture), reveals that stereotypes - whether it be positive or negative - in Philippine society are still very strong. The data gathered proved that impressions regarding Filipino ethnic-inspired apparel are also based on the physical appearance or a garment and what it contributes to an image that an individual has or wants to project (i.e., cool, fashionable, rich in details, maganda). Filipino ethnic-inspired apparel available in the market at the moment is invariably adaptations, reinterpretations, and innovations of traditional ethnic costumes by contemporary designers. However, this is not to say that they are entirely inauthentic. As evidenced by the results of the survey, these "modern ethnic" garments have very much been accepted as a clothing fashion right now - one of the requisites for any innovation to be considered authentic.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Ethnic costume